A Hybrid PWM Technique to Improve the Performance of Voltage Source Inverters - Arif Ahmed (688976) (2023)
Due to the rapid advancement of power semiconductor devices, the use of voltage source inverters (VSIs) has gained widespread acceptance. As a consequence, the performance of the voltage source inverter has emerged as a critical aspect that is highly reliant on the modulation strategy. The pulse width modulation (PWM) technique is the most widely utilized method of controlling power semiconductor switches of VSI. Power quality is always considered as an industrial concern for VSI-based power system such as grid-connected renewable energy systems and industrial motor drives which largely depends on the PWM technique used for switching. However, the existing PWM schemes for VSIs suffer from high total harmonic distortion (THD) and power loss problems. To mitigate the THD and power loss of VSI, a hybrid PWM technique has been proposed in this paper. The proposed hybrid PWM technique introduces a modified modulating signal along with newly shaped carrier signal. A two-level VSI is used to evaluate the performance of the proposed hybrid PWM technique both for with and without filter conditions against RL load. The proposed hybrid PWM technique offers 0.89% filtered voltage THD and 0.69% filtered current THD which are lower than that of existing PWM techniques. On the contrary, at without filter condition, the proposed hybrid PWM technique shows THDs of 45.77% and 12.50% for inverter output voltage and current, respectively which are also lower than those of existing PWM techniques. Apart from these, the proposed hybrid PWM technique reduces the switching and conduction power losses of the VSI as compared to existing PWM techniques. The simulation works are carried out in MATLAB/Simulink environment and a reduced scale experiment is conducted in laboratory to evaluate the performance of the proposed hybrid PWM technique. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3235791